EDUCATIONAL AND PROFESSION MAPPING FIELD OF VISUAL COMMUNICATION DESIGN FOR VOCATIONAL HIGH SCHOOL - Zikrillah (NIM: 27115028), Abdu
Education and profession in the field of Visual Communication Design is currently experiencing rapid growth and shows a fairly complex situation. The existence of problems in the implementation of Visual Communication Design education in Vocational Education level, they are the unmatched link and match between vocational schools and their industry, the competence of expertise has not yet seen the focus on their respective specialist competence. The research method used qualitative method which emphasizes on field observation and interview, which then continued with competency mapping method in mapping the competence of existing expertise based on the science of Visual Communication Design. This mapping also connects the creative industries related to the field of Visual Communication Design and its profession to the existing skill competencies in Vocational Education. So obtained a link and match between Visual Communication Design Education in Vocational Education level with creative industries. Found seven competence of expertise that have related science in Visual Communication Design field, that is Graphic Design, Graphic Production, Visual Communication Design, Animation, Multimedia, Production and Broadcast of Television Program, and Film Production and Television Program. The creative industries of such competence are Advertising, Design, Film, Video, Photography, Interactive Games, Publishing, Printing, and Television. Examples of his profession are junior graphic designer, print operator, cameraman TV, 3D